2019
DOI: 10.2174/1874282301913010043
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Models for Estimating Tropospheric Radio Refractivity Over Osogbo, Nigeria

Abstract: Background:Estimation of tropospheric radio refractivity is significant in the planning and design of terrestrial communication links.Methods:In this study, the monthly average daily atmospheric pressure, relative humidity and temperature data obtained from the National Aeronautics and Space Administration (NASA) during the period of twenty two years (July 1983 - June 2005) for Osogbo (Latitude 7.470N, Longitude 4.290E, and 302.0 m above sea level) were used to estimate the monthly tropospheric radio refractiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…and the radio refractivity of the wet term is given by equation (3) through expansion of equation ( 2) (Akpootu and Rabiu, 2019;Akpootu et al, 2024). Nwet = 3.73 x 10 5 đť‘’đť‘’ 𝑇𝑇 2…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and the radio refractivity of the wet term is given by equation (3) through expansion of equation ( 2) (Akpootu and Rabiu, 2019;Akpootu et al, 2024). Nwet = 3.73 x 10 5 đť‘’đť‘’ 𝑇𝑇 2…”
Section: Methodsmentioning
confidence: 99%
“…The refractivity gradient is obtained by differentiating equation ( 7) with respect to h, therefore, the refractivity gradient is given by (Akpootu et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…They discovered also that the sub-refraction condition which is common from January to May and August to December while superrefraction was noticed predominantly between June and July respectively. Akpootu et al (2019) developed empirical models for estimating tropospheric radio refractivity in Osogbo, Nigeria. In another study, Akpootu et al (2021a) estimated and investigate the variability of tropospheric radio refractivity and radio field strength over Accra Ghana, the result of their study revealed that tropospheric radio refractivity is higher during the rainy season than in the dry season in the months of April and January with 384.356 N-units and 371.6318 N-units respectively.…”
Section: Introductionmentioning
confidence: 99%